"All the Progress to Be Made Will Be Made by Maladjusted Negroes": Mae Mallory, Black Women's Activism, and the Making of the Black Radical Tradition. Issue 2 (15th October 2018) - Farmer, Ashley D
Abstract: Mae Mallory (1927–2007) was a radical political activist and a self-proclaimed "maladjusted Negro." She played a foundational role in developing and sustaining the black freedom movement through her school desegregation protests in the 1950s, Black Power advocacy in the 1960s, and Pan-African and prisoner's rights organizing in the 1970s and 1980s. She also espoused a politics defined by her commitment to a black, community-centered, working-class, gender-conscious, and anti-imperialist worldview. Mallory's multifaceted organizing, intellectual production, and women-centered approach to radical politics have made her an outlier in traditional historical frameworks. However, her alternative intellectual and activist path is also generative in that it illuminates different aspects of black women's political activism. This article examines Mallory's organizing and intellectual production through the lens of "maladjustment." It argues that her unconventional identifications, politics, and organizing trajectory not only showcase Mallory's unique influence on the black radical tradition, they also offer an opportunity to rethink existing approaches to the study of black women's activism. The essay offers one of the first overviews of Mallory's life, organizing, and theorizing, in order to foreground her role in shaping multiple facets of black organizing. In doing so, it offers a larger commentary on how "maladjusted" women like Mallory challenge conventional narratives about the periodization, strategies, and legacies of the black freedom movement.